PENGARUH JENIS WATER SPRAYER TERHADAP EFEKTIVITAS DIRECT EVAPORATIVE COOLING TANPA MENGGUNAKAN COOLING PAD - Nugroho Epri Isnandi; Bambang Yunianto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Evaporative cooler technology originated from the concept of cooling the air with water media. Where the air is cooled by means of direct contacting between water and air , resulting in heat transfer from the air to the water which resulted in the evaporation process , so that the air temperature down and the humidity was rising value . This study aimed to determine effect of water sprayer on the direct evaporative cooler . The study was conducted with the experiment . Research variable is the type of water sprayer with a variation of 1, 5 and 7 holes. The data captured includes data input temperature , RH input , output temperature and RH output . These data are used to determine the decrease in DBT ( Dry Bulb Temperature) , and WBT ( Wet Bulb Temperature) . The result of the calculation is shown in tables and graphs and analyzed based on existing theory. The results showed that the type of water sprayer affect the temperature decrease and increase air humidity output direct evaporative cooler which affect the effectiveness. In direct evaporative cooler mounting holes have a water sprayer 1 effectiveness by 90% which is highest among the water sprayer which only has 5 holes effectiveness of 78% and a water sprayer 7 holes with a 74% effectiveness.